2013
DOI: 10.1016/j.ophtha.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Basis of Variations in Retinal Pigment Epithelium Autofluorescence in Eyes with Geographic Atrophy

Abstract: Purpose Lipofuscin contained in the retinal pigment epithelium (RPE) is the main source of fundus auto-fluorescence (FAF), the target of an imaging method useful for estimating the progression of geographic atrophy (GA) in clinical trials. To establish a cellular basis for hyperfluorescent GA border zones, histologic autofluorescence (HAF) was measured at defined stages of RPE pathologic progression. Design Experimental study. Participants and Controls Ten GA donor eyes (mean age ± standard deviation, 87.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
137
3
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(154 citation statements)
references
References 45 publications
11
137
3
3
Order By: Relevance
“…This is a familiar problem for those using in vivo imaging methods. Many of the RPE cell morphologies seen in the later stages of AMD, such as multilayered cells and heaping and sloughing of cells could disrupt our ability to see cellular structure [5]. The AF imaging technique in FAOSLO capitalizes on the fact that the normal RPE is arranged in a flat monolayer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a familiar problem for those using in vivo imaging methods. Many of the RPE cell morphologies seen in the later stages of AMD, such as multilayered cells and heaping and sloughing of cells could disrupt our ability to see cellular structure [5]. The AF imaging technique in FAOSLO capitalizes on the fact that the normal RPE is arranged in a flat monolayer.…”
Section: Resultsmentioning
confidence: 99%
“…Histological studies of postmortem eyes have shown that substantial changes occur in RPE cell mosaic morphology in AMD [4,5]. These changes may precede and/or accompany RPE cell death and the degeneration of overlying photoreceptors [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is notable that no hyperautofluorescence was noted, suggesting that these HPS are not mainly made of lipofuscin. 38 Differently form reticular pseudodrusen, which are characterized by progressive reabsorption and migration of the hyperreflective material in the inner retinal layers before the development of GA, HPS appear as heterogeneous hyperreflective structure accumulating in the context of GA. 32,33 Alternatively, HPS could be compared with soft drusen. Soft drusen are yellowish with indistinct margins, bigger than hard drusen, confined to the macula, precursor to choroidal neovascularization, and consisting in focal accentuations of basal linear deposits, specific for AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Inquiries to Marc Biarnés, C/ Vilana 12, Office 90, Institut de la màcula i de la retina, Centro Médico Teknon, Barcelona, Spain; e-mail: biarnes@ oo.upc.edu Nonetheless, the role of lipofuscin in GA pathogenesis remains controversial. Most studies 6,[8][9][10] suggest that it has deleterious effects on RPE that may lead to cell death and GA progression, while other clinical 11,12 and basic research findings 13,14 do not support this hypothesis. Indeed, a visual cycle modulator did not meet the primary efficacy endpoint in a phase II clinical trial.…”
mentioning
confidence: 99%